Goods distribution management in city logistics environment: A systemic approach - Vasileios Zeimpekis (Advances in Management & Applied Economics, 2011)
The routing plan of a delivery fleet is usually developed a priori and provides an optimal (or near optimal) way of serving customers by taking into account certain constraints, such as vehicle capacity and delivery time windows. However, such plans may not cope adequately in a city logistics environment, in which unexpected events often occur during delivery execution (e.g. adverse traffic conditions). These events may lead to delays, higher costs, and inferior customer service. This paper presents the development and evaluation of a real-time fleet management system that handles such unforeseen events by using advanced traffic forecasting techniques and rerouting strategies coupled with telematic technology. The system monitors the delivery vehicles in real time, detects deviations from the initial distribution plan, and adjusts the schedule accordingly, by suggesting effective rerouting strategies. The system has been tested in real-life cases and the results show that delivery performance is enhanced significantly and customer satisfaction is improved accordingly.
Keywords: R41; R31; 330; urban freight distribution; real-time vehicle routing; dynamic incident handling